Psychological Resilience among Left-Behind Children in a Rural Area of Eastern China - Binyan Wang; Lihong Ye; Linshuoshuo Lv; Wei Liu; Fenfen Liu; Yingying Mao (MDPI AG, 2022)
Childhood is an important period for individuals' psychological development. Due to long-term separation from the parents, left-behind children (LBC) more easily develop deviation in cognition and abnormal personality. In this study, we aimed to explore the status of psychological resilience among LBC in a rural area of eastern China. We carried out a cross-sectional survey including middle and high school students from Qingyuan County of Zhejiang Province. Psychological resilience was measured using a modified scale developed for Chinese children. Data from a total of 1086 participants were collected, and the mean ± standard deviation score of psychological resilience was 4.11 ± 0.42. Multivariable linear regression analyses revealed that being a class leader (p = 0.010) and having high self-evaluation of academic performance (p < 0.001) were related with psychological resilience. Moreover, high contact frequency between parents and children (p = 0.019) was associated with better psychological resilience among LBC. In conclusion, we found that being a class leader and having high self-evaluation of academic performance were associated with better psychological resilience among the children in this rural area and contact between parent and child was an essential factor associated with psychological resilience among LBC.